Investigation of ZnCo2O4–Pt hybrids with different morphologies towards catalytic CO oxidation. Issue 48 (24th November 2015) - Wang, Fan; Wang, Xiao; Liu, Dapeng; Zhen, Jiangman; Li, Junqi; Zhang, Hongjie
Abstract : In this work, three kinds of ZnCo2 O4 morphologies, that is, rod, plate and sphere, have been successfully prepared and further used to support Pt nanoparticles (NPs) via in situ deposition. Abstract : In this work, three kinds of ZnCo2 O4 morphologies, that is, rod, plate and sphere, have been successfully prepared and further used to support Pt nanoparticles (NPs) via in situ deposition. The as-prepared ZnCo2 O4 –Pt hybrid nanomaterials were then carefully characterized by SEM, TEM, XRD, XPS, ICP EDX, and N2 adsorption measurement in great detail. Besides, the three catalysts were also evaluated by the model reaction of catalytic CO oxidation. After comparing the difference in the three kinds of morphologies, we have tried to clarify the reason for their different catalytic performances. As a result, the ZnCo2 O4 –Pt sphere was found to be the most active, attaining 100% CO conversion at a relatively low temperature of 140 °C, because more Pt NPs are prone to distribution on the surface of ZnCo2 O4 spheres than the other ones. The following cycling tests confirm the excellent stability of the as-prepared ZnCo2 O4 –Pt samples.